PATOFISIOLOGI DAN PENATALAKSANAAN NEFROPATI RADIOKONTRAS - Sanjaya, Surya; Suwitra, Ketut (journal of internal medicine, 2009)
Contrast induced nephropaty (CIN) was recognized as one of the leading causes of acute renal failure in patient withrenal insufficiency, diabetes mellitus, volume depletion and low cardiac out put. The incidence of CIN is estimated to be 1 Ð 2%in the general population, but the relative risk is greatly increased in diabetics, the elderly, and those with intrinsic renal disease,congestive heart failure, and dehydration. CIN is defined by an increase in creatinine 0.5 mg/dL or 25% from baseline that occurs2 Ð 3 days after contrast administration. A reduction in renal perfusion caused by a direct effect ofcontrastmedia on the kidneyand toxic effects on the tubularcells are generally accepted as the main factors in the pathophysiologyof contrastmedium inducednephropathy. Pathological changes induced by contrastmedium are epithelialcell vacuolization, interstitial inflammation andcellular necrosissuggest a direct toxic effect of contrastmedia on renal tubularepithelial cells. Several measures have beenrecommended to prevent contrastinduced nephropathy,which include: volume expansion, hydrationwith intravenous administrationof normal saline, infusion of mannitol, theophylline, dopamine,acetylcysteine, use of iso-osmolar non-ionic contrastmediainsteadof low-osmolarnon-ionic or high-osmolar ionic contrast,haemofiltration rapidly after contrast administration, injectionofsmall volume of contrast medium, gadolinium based contrastmedia